دور القرآن الكريم في تهذيب المجتمع - Zamsuhaila Bt Zaid; زامسو هايلا بنت ذيد (Universiti Sains Islam Malaysia, 2022)
The writer was used the library research to completed this research, which take any suitable information from books and articles. This topic is the role al Quran al Karim in forming society. The writer divided the research into three main chapters. First chapter it includes the meaning of the al Quran al Karim in "language" and "istilah". Beside that this research also discuss about position of a1 Quran a1 Karim as a legislation Islam resource and than discuss also about others name of al Quran al Karim, how many "ayat" and "Surah" in Quran, "ayat Makki" and "Madani" and others. The second chapters discuss about method of lowered a1 Quran al Karim from Allah to prophet Muhammad SAW, method of collection and writing of al Quran a1 Karim at occasions prophet Muhammad SAW, occasions khalifah Abu Bakar a1 Siddiq, and khalifah Usman bin Affan. The third chapter was discussing about the role of al Quran a1 Karim in forming society. As we know a1 Quran al Karim is foundation resource in legislation of Islam. It function is given more information to Muslim's and teaching Muslim's obey of Allah instruction. It also became foundation resource in all matter included of ibadah, muamalah, economic, politic and others. It contents included hukum and guidelines need to obey for Muslim's. From this research we know the Quran al Karim is hold main role in forming society.